Characterization of semiconductor heterostructures and nanostructures - Lamberti, Carlo; Lamberti, Carlo; Peressi, Maria; Baldereschi, Alfonso; Baroni, Stefano; Cavallini, Anna (Elsevier, 2008)
Characterization of Semiconductor Heterostructures and Nanostructures is structured in chapters, each one devoted to a specific characterization technique used in the understanding of the properties (structural, physical, chemical, electrical etc.) of semiconductor quantum wells and superlattices. A chapter is devoted to the ab initio modeling. The book has basically a double aim. The first one lies on the educational ground. The book provides the basic concept of each of the selected techniques with an approach understandable by master and PhD students in Physics, Chemistry, Material Science, Engineering, Nanotechnology. The second aim is to provide a selected set of examples from the recent literature of the TOP results obtained with the specific technique in understanding the properties of semiconductor heterostructures and nanostructures. Each chapter has this double structure: a first part devoted to explain the basic concepts, providing the larger possible audience, and a second one to the discussion of the most peculiar and innovative examples, allowing the book to have the longer possible life time. Of course, the book is devoted to the specialized subset of scientists working in the fields of design, growth, characterization, testing of heterostructures-based devices in both academic and industrial laboratories. But the final goal is somewhat more ambitious, and in this regard the topic of quantum wells, wires and dots should be seen as a pretext of applying top level characterization techniques in understanding the structural, electronic etc properties of matter at the nanometer (even sub-nanometer) scale.